Determination of Selenium, Lead, and Zinc Levels in Well Water Using the AAS Method - Khoirul Ngibad (Universitas Negeri Yogyakarta, 2023)
Metal selenium (Se) has long been identified as a toxic element. In addition, the presence of lead metal (Pb) in waters is harmful both directly to the life of organisms and its effects indirectly on human health. Further, Zn metal can cause system dysfunction resulting in decreased growth and reproduction. This study aims to analyze Se, Pb, and Zan on well water around the Taman District, Sidoarjo Regency. The method used in this study is the AAS method at 196 nm for measuring Se levels, 283.3 nm for measuring Pb levels, and 213.9 nm for measuring Zn levels. 0.013; and 0.002mg/L (well water A) and 0.002; 0.013; and 0.002 mg/L (well water B). The Se, Pb, and Zn levels still meet the quality standards (maximum content) of chemical parameters.